EGCG modified small intestine submucosa promotes wound healing through immunomodulation - Nie, Rong; Zhang, Qing-Yi; Tan, Jie; Feng, Zi-Yuan; Huang, Kai; Sheng, Ning; Jiang, Yan-Lin; Song, Yu-Ting; Zou, Chen-Yu; Zhao, Long-Mei; Li, He-Xi; Wang, Rui; et al. (Composites. Part B, Engineering, 2023)
Decellularized porcine small intestinal submucosa (SIS) has shown promising therapeutic efficacy as a functional wound dressing. Nevertheless, its limited anti-oxidative and immunomodulatory capacities have restricted its application for the treatment of complex skin wounds. Herein, epigallocatechin gallate (EGCG), a polyphenolic compound, was employed for the modification of the SIS to overcome such shortcomings. The EGCG-modified SIS (E-SIS) has shown excellent biocompatibility and improved hydrophilicity for cell adhesion. Notably, in vitro studies showed that the E-SIS could effectively alleviate oxidative stress and facilitate the M1-to-M2 phenotype transition of macrophages, thereby creating a favorable immune microenvironment for cell proliferation, migration, collagen synthesis as well as angiogenesis. A full-thickness skin defect model, combined with macrophage depletion, has further confirmed that the E-SIS could accelerate skin wound repair through immunomodulation in vivo. This suggested that the EGCG modification could provide a facile yet effective method to broaden the applications of the SIS for skin wound management.